EARTHQUAKE HAZARD ZONATION OF PELABUHANRATU AREA USING ANALYTICAL HIERARCHY PROCESS (AHP) - YASIN SULISTYAWATI, ELITE
Pelabuhanratu area is prone to earthquakes because this area is close to Cimandiri and Citarik Faults zone and the plate boundary zone between Eurasian Continental and Indo-Australian Oceanic Plates. This plate boundary generates a convergent boundary, which called as subduction zone. The main and dangerous earthquakes sources in this area are possible from the presence of Cimandiri and Citarik Faults. According to this situation, it is necessary to carry out an earthquake hazard zonation, which in turn useful for mitigation and land use planning. Analyses within this study were conducted on six parameters which might influence in the earthquake hazards: morphology, lithology, geological structure, earthquake sources, peak ground acceleration and earthquake intensity. The Analytical Hierarchy Process Method is used to weighting of each parameter. The results of weighting are then used to earthquakes hazard zonation by means of Geographic Information Systems (GIS). The results obtained from the analyses show five earthquake hazard zones, which are very high, high, medium, low and very low. Very high earthquake hazard zone cover an area of 2320.04 ha (25.23%), located along the coastal plain area of Alluvial Deposits at the southern part of Pasarsuren, Cikadu, Pelabuhanratu, Tonjong and Citarik Villages. High earthquake hazard zone has an area of 3217.37 ha (34.99%), covering the northern part of the Citarik, Pelabuhanratu, Cikadu and Pasarsuren Villages as well as at the center of Citarik and Tonjong Villages. Medium earthquake hazard zone cover an area of 1411 ha (15.35%), including the most part of Citepus and Cikadu Villages. Low earthquake hazard zone has an area of 2191 ha (23.83%), covering the most of Cibodas and Buniwangi Villages, meanwhile very low earthquake hazard zone cover an area of 55.19 ha (0.6%), mainly at the northern part of Buniwangi Village.